PENDAMPINGAN PENASIHAT HUKUM TERHADAP TERDAKWA HUKUMAN PIDANA PENJARA DI ATAS 5 TAHUN : Legal Counsel Assistance For Defendants With Prison Sentences Exceeding 5 Years - Christina , Anggi Erika; Setiyono (Faculty of Law, Universitas Trisakti, 2024)
Defendants who are sentenced to imprisonment for more than 5 years have the right to be accompanied by legal counsel. The formulation of the problem raised concerns the reason in examining the accused at the trial of a crime which carries a penalty of more than 5 (five) years in prison without beng accompanied by a legal adviser and the legal consequences of the decision handed down to the accused Tito Ariyanto who was examined and sentenced without beng accompanied by a legal adviser . This research method uses reAArch types based on normative research referring to secondary data. The nature of the research is descriptive and drawing conclusions using deductive methods. The results of the research and discussion, namely the actions of the defendant as a delivery agent for crystal methamphetamine/ecstasy were sentenced to imprisonment for 9 (nine) years without beng accompanied by legal counsel, so the conclusion of this investigation, the legal consequences caused by the defendant not beng accompanied by legal counsel, were not clearly explained by the law, but if you see several decisions of the Supreme Court then it becomes procedural law, that it is explained that if the defendant is not accompanied by legal counsel, then all legal products produced are null and void and contain legal defects